Comparison of the Effectiveness of Online Narrative Therapy and Cognitive Behavioral Therapy on Mental Health and Adherence to Treatment in Cancer Patients with Low Psychological Hardiness - Banisafar, Afshin; Ahi, Qasem; Mansouri, Ahmad; Bahrainian, Abdolmajid (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: Cancer is among the diseases that can cause various psychological issues for its sufferers, necessitating the discovery of effective methods to assist these individuals. This research aimed to compare the effectiveness of online narrative therapy and cognitive-behavioral therapy on mental health and adherence to treatment in cancer patients with low psychological hardiness. Methods and Materials: This was a quasi-experimental study conducted using a pre-test-post-test design with two experimental groups and one control group. The study population comprised all cancer patients attending hospitals in Tehran in 2022. The sample consisted of 45 patients selected through purposive sampling and randomly assigned to three groups: online narrative therapy, cognitive-behavioral therapy, and a control group. Data were collected using the General Health Questionnaire by Goldberg and Hiller (1972) and the Treatment Adherence Scale by Madanloo (2018). Data were analyzed using MANCOVA and Bonferroni post-hoc tests with SPSS software version 22. Findings: Results indicated significant differences between the online narrative therapy and cognitive-behavioral therapy groups in terms of general health dimensions (physical health, anxiety, and social functioning disturbance) (P<0.01), with online narrative therapy showing greater effectiveness in these dimensions. However, no significant difference was found in treatment adherence between the online narrative therapy and cognitive-behavioral therapy groups. Conclusion: According to the findings of this study, both narrative and cognitive-behavioral therapies can be effective methods for improving mental health and treatment adherence in cancer patients. In this context, online narrative therapy may be more efficient.